"I Forgive Him, Yes": Gendered Trauma Narratives of the Texas Tower Shooting - Kähkönen Lotta (Brill, 2022)
The Tower shooting at The University of Texas at Austin on August 1, 1966 is among the first and most memorable mass shootings in U.S. history because of its wide media coverage. Drawing from theorization of cultural trauma and trauma cultures after World War II, this chapter explores the mediation and narrativization of the Tower shooting as a cultural trauma. In this framing, trauma is a product of history and politics, and subject to reinterpretation. The chapter takes a closer look at the KTBC special news report aired immediately after the shooting, and two narratives: Elizabeth’s Crook’s novel Monday, Monday (2014) and Keith Maitland’s animated documentary film Tower (2016), created in response to a collective need for commemoration several decades later. The narratives reify a particular imagery that shapes the collective trauma and its affective resonance. The chapter focuses on the gendered figures of heroes, victims, and survivors in constituting the collective trauma that emerges as a result of a cultural crisis. How are these figures highlighted in the narratives? What cultural values and concerns relating to mass shootings as traumatizing experiences does the gendered imagery reveal? An analysis of gendered heroes, victims, and survivors brings perspectives on the pervasive cultural mode in which the collective trauma of mass shooting is processed within U.S. gun culture.
Up in Arms: Gun Imaginaries in Texas